Impact of Land Uses on Surface Water Quality and Associated Aquatic Insects at Parwanoo Area of Solan District of Himachal Pradesh, India - Gupta, Kavita; Verma, S. C.; Thakur, Meena; Chauhan, Aakriti (International Journal of Bio-resource and Stress Management, 2023)
Study on water quality, its seasonal variation, type and diversity of aquatic insect fauna and quality of surface water during different seasons and under different land uses of Parwanoo area of Solan district of Himachal Pradesh was conducted during rainy, winter and summer seasons under different land uses. Samples of surface water from different sources under different land uses (agriculture, forest and urban) were collected and analysed for quality parameters viz. pH, temperature, electrical conductivity, total dissolved solids, biological oxygen demand( BOD), chemical oxygen demand(COD), Ca, Mg, NO3, and Cl contents. The contents of all the elements were within permissible limits except Ca (>75 mg l-1). Aquatic insects found in surface water were identified up to family level and Simpson Biodiversity, EPT and family biotic indices were calculated.